ҚАРАҚАЛПАҚСТАНДА БИЛИМЛЕНДИРИЎ ТАРАЎЫН КОМПЬЮТЕРЛЕСТИРИЎ ҲӘМ ЖӘМИЙЕТТИ ИНФОРМАТИЗАЦИЯЛАЎДЫҢ БАСҚЫШЛАРЫ - Атаджанов, Х. (ILIM hám JÁMIYET, 2018)
The issues of informatization of the society, providing it with all necessary eguipment and information were and remain to be one of the actual problems at different tims. First of all, it’s necessary to begin informatization in the education system and in the field of science, only in this case we’ll achieve good results. The article contains the information about the beginning of the first electronic teaching.